Legal and Humanistic Approaches to Medical Procedure Refusal - Susilo, Dody Hendro; Jamaludin, Ahmad (LifeSciFi, 2025)
The refusal of medical treatment by patients, grounded in deeply held personal or religious beliefs, presents a profound legal and ethical dilemma, colliding with the healthcare professional’s fundamental duty to preserve life. This study analyzes this dilemma from both normative and humanistic perspectives. This study employs a qualitative, doctrinal methodology, synthesizing a literature review of national and international legal regulations, bioethics, health law, and academic sources published between 2013 and 2024. The analysis reveals three core findings: Patients possess a robust, legally protected right to autonomy and religious freedom; Healthcare professionals are bound by an equally compelling legal and professional obligation to provide care, particularly in emergencies; and a significant tension exists where rigid legal-formalistic solutions (normative) fail to address the underlying humanistic considerations of patient dignity. The study argues for an integrative normative-humanistic framework. This model reconciles the conflict by moving beyond legal formalism to emphasize therapeutic communication and participatory-dialogic solutions. This integration minimizes disputes by ensuring legal certainty for physicians while respecting patient dignity. This research concludes that this integrated approach is essential for providing just, ethical, and humane resolutions in multicultural societies.